2020
DOI: 10.1002/slct.202001230
|View full text |Cite
|
Sign up to set email alerts
|

Pimenta dioica Mediated Biosynthesis of Gold Nanoparticles and Evaluation of Its Potential for Theranostic Applications

Abstract: In recent years, gold nanoparticles have emerged as promising agents for plasmonic sensing, photoacoustic imaging, photothermal therapy, and other biomedical applications. In this work, green synthesis of plant‐mediated gold nanoparticles (AuNPs) using an aqueous leaf extract of Pimenta dioica was carried out and the synthesized nanoparticles were characterized using X‐ray diffraction (XRD), ultraviolet‐visible (UV‐Vis) absorption spectroscopy, Fourier transform infra‐red (FTIR) spectroscopy, and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Consistent with literature reports [ 36 ], we observed that the average size of SP-AuNPs and SP-AgNPs was 5–30 nm and 10–40 nm, respectively. In a previous study, AuNPs obtained through a simple plant-mediated approach were highly monodispersed and spherical, with a size of 4 nm [ 37 ].…”
Section: Resultssupporting
confidence: 92%
“…Consistent with literature reports [ 36 ], we observed that the average size of SP-AuNPs and SP-AgNPs was 5–30 nm and 10–40 nm, respectively. In a previous study, AuNPs obtained through a simple plant-mediated approach were highly monodispersed and spherical, with a size of 4 nm [ 37 ].…”
Section: Resultssupporting
confidence: 92%
“…The peaks at 1340, 1210, and 1070 cm -1 correspond to the asymmetric and symmetric C-O-C stretching mode, respectively, which confirms the presence of the methoxy group on the benzene ring of eugenol [32]- [34]. These peaks are consistent with the FTIR peaks of functional groups of eugenol, present in the Pimenta dioica plant [28].…”
Section: Ftir Spectroscopy and X-ray Diffraction Analysissupporting
confidence: 79%
“…The occurrence of carboxylic acid, alkyl halides alkanes, and miscellaneous functional groups in P. dioica leaves have been reported by Murali et al [27]. Kharey et al [28] obtain green synthesized gold nanoparticles (AuNPs) using aqueous leaf extract of Pimenta dioica.…”
Section: Introductionmentioning
confidence: 95%